Variation in body composition during the ramadan fast in athletes following a varied sports training program: intersex variations - Nizar Lotfi; Mohammed Madani (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objective. Ramadan fasting, characterized by diurnal abstinence from food and water, can significantly impact body composition, particularly in athletes undergoing intense training. This study aimed to evaluate gender-specific variations in body composition among university athletes following a varied sports training program during Ramadan.